"This pregnancy makes sense": Experiences of women who have decided to continue pregnancy after lethal fetal diagnosis. Issue 2 (7th February 2023) - Tataj-Puzyna, Urszula; Węgrzynowska, Maria; Ryś, Maria; Sys, Dorota; Bączek, Grażyna; Baranowska, Barbara
Abstract: Lethal fetal diagnosis defines severe developmental disorders that lead to the death of a fetus or newborn. Using semi-structured interviews, we explored the experiences of women in Poland who actively decided to continue with the pregnancy after diagnosis. We thematically analyzed data collected from 10 women. We identified four themes: pregnancy as an experience of prenatal motherhood; the child as person; birth as encounter and farewell; and the mother experience in retrospect. This study was conducted while the termination of pregnancy due to the irreversible fetal abnormality was legal in Poland. Since October 2021, it is no longer legal.